Identification of osteoclast-osteoblast coupling factors in humans reveals links between bone and energy metabolism - Megan M. Weivoda (Nature Portfolio, 2020)
Anti-resorptive bone therapies also inhibit bone formation, as osteoclasts secrete factors that stimulate bone formation by osteoblasts. Here, the authors identify osteoclast-secreted factors that couple bone resorption to bone formation in healthy subjects, and show that osteoclast-derived DPP4 may be a factor coupling bone resorption to energy metabolism.